The Value Relevance of Accounting Information on The Holdings of Cryptocurrencies - Nur Astri Sari; Isnalita (Universitas Swadaya Gunung Jati, 2026)
This study investigates the value relevance of accounting information for cryptocurrency holdings under the IFRS Interpretations Committee’s (IFRS IC) agenda decisions. It examines whether the classification of cryptocurrencies as intangible assets (IAS 38) or inventories (IAS 2) influences the decision-usefulness of accounting information in explaining share prices. The analysis is grounded in the Ohlson (1995) valuation model. Using a sample of IFRS reporters with holdings of cryptocurrency, this study employs regression analysis to test the association between share prices and key financial metrics, including book value of equity per share, earnings per share, and a dummy variable representing cryptocurrency classification. The results indicate that traditional accounting metrics book value of equity and earnings per share remain highly relevant in explaining share prices. However, the classification of cryptocurrency holdings under IAS 2 or IAS 38 does not significantly contribute to share price determination. This study extends the value relevance literature by focusing on the emerging asset class of cryptocurrencies.